Holistic Model of Celebrity Endorsement in Political Marketing - Mikuláš, Peter (Political Preferences, 2016)
The aim of the paper is to provide useful tools for integral look at the celebrity endorsement process in political marketing that results in a holistic concept. The need for its creation was initiated by several authors, highlighting the inadequacy of partial approaches and thus limited possibilities for the application of the existing models. Today, the main shortcomings of existing concepts of the theory and research in the field of celebrity endorsement lie in its fragmentation and inconsistency. The proposed model, based on theoretical research, has the ambition to open up a wider debate on the issue and to provide a practical tools for a better understanding of the phenomenon. Key words: celebrity, political marketing, celebrity endorsement, models of celebrity, endorsement